a) $x^2 - 49$
Применяем формулу разности квадратов: $a^2 - b^2 = (a - b)(a + b)$
$x^2 - 49 = x^2 - 7^2 = (x - 7)(x + 7)$
б) $25x^2 - 10xy + y^2$
Заметим, что это квадрат разности: $a^2 - 2ab + b^2 = (a - b)^2$
$25x^2 - 10xy + y^2 = (5x)^2 - 2 * 5x * y + y^2 = (5x - y)^2$
в) $125x^3 - y^3$
Применяем формулу разности кубов: $a^3 - b^3 = (a - b)(a^2 + ab + b^2)$
$125x^3 - y^3 = (5x)^3 - y^3 = (5x - y)((5x)^2 + 5x * y + y^2) = (5x - y)(25x^2 + 5xy + y^2)$
г) $64x^6y^3 - 27a^9$
Применяем формулу разности кубов: $a^3 - b^3 = (a - b)(a^2 + ab + b^2)$
$64x^6y^3 - 27a^9 = (4x^2y)^3 - (3a^3)^3 = (4x^2y - 3a^3)((4x^2y)^2 + 4x^2y * 3a^3 + (3a^3)^2) = (4x^2y - 3a^3)(16x^4y^2 + 12x^2ya^3 + 9a^6)$
Ответ:
a) $(x - 7)(x + 7)$
б) $(5x - y)^2$
в) $(5x - y)(25x^2 + 5xy + y^2)$
г) $(4x^2y - 3a^3)(16x^4y^2 + 12x^2ya^3 + 9a^6)$